Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Implications of improved remote sensing capabilities on blue carbon quantification - Steven W.J. Canty; Miguel Cifuentes-Jara; Jorge Herrera-Silveira; Hannah K. Morrissette; Jordan R. Cissell; Joanna Acosta-Velázquez; Emil Cherrington; Ilka C. Feller; Daniel A. Friess; Jonathan S. Lefcheck; Loraé T. Simpson; Claudia Teutli-Hernandez (Estuarine, Coastal and Shelf Science, 2025)

Using isolation-by-distance to jointly estimate effective population density and dispersal distance: a practical evaluation using bumble bees - Dylan T. Simpson (Oecologia, 2025)
Effective population density and intergenerational dispersal distance are key aspects of population biology, but obtaining empirical estimates of these parameters can be difficult. This is especially true for my study taxa, wild bees. In this paper, I apply and evaluate an existing but underutilized method to estimate effective density and dispersal distance of bumble bees ( Bombus , Apidae). Specifically, using 10 datasets of bumble bees in North America, I use the relationship between genetic isolation-by-distance and Wright’s neighborhood size to define a density-dispersal isocline—that is, a curve describing pairs of density and dispersal values consistent with observed rates of isolation-by-distance. These parameters are inversely related; as one increases the other decreases. I then use outside estimates of bumble bee dispersal distances to make more specific estimates of effective colony density. Compared to some prior estimates of census density (100s to 1000s colonies/km 2 ), my estimated effective colony densities were very low (1–41 effective colonies/km 2 ). I also hypothesize, however, that these estimates are affected by the spatial extent of sampling, due to scale-dependent patterns in the distribution of individuals. To test this hypothesis, I subsampled each dataset to simulate varying study extent, and repeated my analysis. Within populations, effective densities tended to decrease when measured across larger spatial extents. Altogether, I demonstrate a useful and under-appreciated tool for studying population biology, especially of small, mobile animals like bees, but also show that researchers must interpret their results carefully within the context of their study design.

Supplementation strategies to control propionic acid accumulation resulting from ammonia inhibition in dry anaerobic digestion: Osmoprotectants, activated carbon and trace elements - Ildefonso Rocamora; Stuart T. Wagland; Francis Hassard; Raffaella Villa; Miriam Peces; Ioannis A. Fotidis; Edmon W. Simpson; Oliver Fernández; Yadira Bajón-Fernández (Journal of Environmental Chemical Engineering, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

An evaluation of the seasonal Caribbean hydroclimate in low and high-resolution CESM and other CMIP6 models - Carlos J. Martinez; Isla R. Simpson; John T. Fasullo; Andreas F. Prein (Climate Dynamics, 2025)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Ice-marginal volcanic sequence in Iceland found on a nondescript gradual hillslope: An unexpected record of ice thickness late in deglaciation - Audrey R. Putnam; Kirsten L. Siebach; Candice C. Bedford; Sarah L. Simpson; Michael T. Thorpe; Joseph J. Tamborski; Elizabeth B. Rampe (Journal of Volcanology and Geothermal Research, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Challenges to Seagrass Restoration in the Indian River Lagoon, Florida - Vivienne A. Main; Morgan K. Gilligan; Sarah M. Cole; Todd Z. Osborne; Ashley R. Smyth; Loraé T. Simpson (Journal of Marine Science and Engineering, 2024)
Seagrasses provide valuable ecosystem services, including improved water quality, carbon sequestration, and sediment stabilization. Unfortunately, these critical habitats are declining globally due to a range of anthropogenic impacts. Restoration practitioners have made efforts to mitigate loss through the introduction of seagrass transplants. However, seagrass restoration has low success rates and is plagued by water quality concerns and ecosystem degradation. Studies to improve seagrass restoration efforts have targeted different functional taxa to allow for greater stability and recovery of threatened ecosystems, and excluded macro-grazers to limit losses to newly established and restored seagrasses. We hypothesized greater seagrass (Halodule wrightii) health when restored in conjunction with hard clams (Mercenaria mercenaria) and protected from grazers using herbivore exclusion devices (HEDs) in the Indian River Lagoon (IRL), Florida. While our study experienced high rates of seagrass mortality, we were able to observe significant differences in seagrass health between IRL sub-lagoons and observed the positive effects of HEDs on seagrass health. The observed high species mortality highlights how restoration in the IRL is hindered by biotic and abiotic stressors, site selection, and a lack of clear restoration protocols. As we see ongoing declines in water quality and loss of foundational species, informed site selection, greater understanding of grazer presence, and multi-species restoration will provide an informed approach for future seagrass restoration projects globally.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The repeatability of a cycling exercise-heat stress test in a male population - Jake Shaw; E. Cole; Andrew J. Simpson; Christopher J. Tyler; Andrew T. Garrett (Journal of Thermal Biology, 2024)

Response of Root Respiration to Warming and Nitrogen Addition Depends on Tree Species - T. J. Muratore; M. A. Knorr; M. J. Simpson; R. B. Stephens; R. P. Phillips; S. D. Frey (Global Change Biology, 2024)
Roots contribute a large fraction of CO 2 efflux from soils, yet the extent to which global change factors affect root‐derived fluxes is poorly understood. We investigated how red maple ( Acer rubrum ) and red oak ( Quercus rubra ) root biomass and respiration respond to long‐term (15 years) soil warming, nitrogen addition, or their combination in a temperate forest. We found that ecosystem root respiration was decreased by 40% under both single‐factor treatments (nitrogen addition or warming) but not under their combination (heated × nitrogen). This response was driven by the reduction of mass‐specific root respiration under warming and a reduction in maple root biomass in both single‐factor treatments. Mass‐specific root respiration rates for both species acclimated to soil warming, resulting in a 43% reduction, but were not affected by N addition or the combined heated × N treatment. Notably, the addition of nitrogen to warmed soils alleviated thermal acclimation and returned mass‐specific respiration rates to control levels. Oak roots contributed disproportionately to ecosystem root respiration despite the decrease in respiration rates as their biomass was maintained or enhanced under warming and nitrogen addition. In contrast, maple root respiration rates were consistently higher than oak, and this difference became critical in the heated × nitrogen treatment, where maple root biomass increased, contributing significantly more CO 2 relative to single‐factor treatments. Our findings highlight the importance of accounting for the root component of respiration when assessing soil carbon loss in response to global change and demonstrate that combining warming and N addition produces effects that cannot be predicted by studying these factors in isolation.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Drivers of population dynamics of at-risk populations change with pathogen arrival - Alexander T. Grimaudo; Joseph R. Hoyt; R. Andrew King; Rickard S. Toomey; Chris Simpson; Cory Holliday; Alexander Silvis; Rick T. Doyle; Joseph A. Kath; Mike P. Armstrong; Virgil Brack; Richard J. Reynolds; et al. (Biological Conservation, 2024)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Leveraging wastewater surveillance to detect viral diseases in livestock settings - Warish Ahmed; Yawen Liu; Wendy Smith; Wayne Ingall; Michael Belby; Aaron Bivins; Paul Bertsch; David T. Williams; Kirsty Richards; Stuart Simpson (Science of The Total Environment, 2024)

Testing in-situ apatite Lu–Hf dating in polymetamorphic mafic rocks: a case study from Palaeoproterozoic southern Australia - Dillon A. Brown; Anthony Reid; Elizabeth A. Jagodzinski; Megan Williams; Alex Simpson; Mark Pawley; Christopher L. Kirkland; Claire Wade; Alexander T. De Vries Van Leeuwen; Stijn Glorie (Contributions to Mineralogy and Petrology, 2024)
In mafic systems where primary mineral assemblages have witnessed moderate- to high-temperature hydrous overprinting and deformation, little is known about the retentivity of the Lu–Hf isotopic system in apatite. This study presents apatite laser-ablation Lu–Hf and U–Pb geochronology, zircon geochronology, and detailed petrological information from polymetamorphic mafic intrusions located in the central-western Gawler Craton in southern Australia, which records an extensive tectonometamorphic history spanning the Neoarchaean to the Mesoproterozoic. Zircon records magmatic crystallisation ages of c. 2479–2467 Ma, coinciding with the onset of the c. 2475–2410 Ma granulite-facies Sleafordian Orogeny. The amphibole-dominant hydrous assemblages which extensively overprint the primary magmatic assemblages are hypothesised to post-date the Sleafordian Orogeny. The Lu–Hf and U–Pb isotopic systems in apatite are used to test this hypothesis, with both isotopic systems recording significantly younger ages correlating with the c. 1730–1690 Ma Kimban Orogeny and the c. 1590–1575 Ma Hiltaba magmatic event, respectively. While the early Mesoproterozoic apatite U–Pb ages are attributed to thermal re-equilibration, the older Lu–Hf ages are interpreted to reflect re-equilibration facilitated primarily by dissolution-reprecipitation, but also thermally activated volume diffusion. The mechanisms of Lu–Hf isotopic resetting are distinguished based on microscale textures and trace element abundances in apatite and the integration of apatite-amphibole textural relationships and temperatures determined from the Ti content in amphibole. More broadly, the results indicate that at low to moderate temperatures, apatite hosted in mafic rocks is susceptible to complete recrystallisation in rocks that have weak to moderate foliations. In contrast, at higher temperatures in the absence of strain, the Lu–Hf system in apatite is comparatively robust. Ultimately, the findings from this study advance our understanding of the complex role that both metamorphism and deformation play on the ability of mafic-hosted apatite to retain primary Lu–Hf isotopic signatures.

Geometric effects of fragmentation are likely to mitigate diversity loss following habitat destruction in real‐world landscapes - Colleen Smith; Juan A. Bonachela; Dylan T. Simpson; Natalie J. Lemanski; Rachael Winfree (Global Ecology and Biogeography, 2024)
Aim Habitat conversion is the number one threat to biodiversity. The loss of biodiversity due to habitat loss might be exacerbated if species are harmed by fragmentation per se—the breaking apart of natural habitat that remains (hereafter fragmentation ). However, the evidence that species are harmed by habitat fragmentation is mixed. Studies at the patch scale tend to show that fragmentation reduces diversity due to negative demographic effects on species' dispersal, survival and fecundity. In contrast, studies at the landscape scale tend to show that fragmentation increases diversity. This discrepancy may be partly due to geometric effects, defined as greater species turnover between patches in more fragmented landscapes. Although these effects have been demonstrated theoretically and are expected to be stronger across larger spatial extents, it is unclear whether they are likely to occur in real‐world settings with both realistic landscape patterns and communities. Here, we investigated the possibility of geometric effects using simulations combined with real‐world landscape and community data. Location New Jersey, northeastern USA. Time period Current. Taxa studied Bees. Methods We focused on landscape sizes within the typical range for protected areas (36–576 ha), simulated forest loss using real landscape patterns, and simulated forest‐bee communities based on field data we collected. Results We found weak but positive effects of fragmentation: immediately following forest destruction, the most fragmented forests harboured up to 7.3% more species than the least fragmented forests of the same area, in agreement with observational studies of biodiversity along fragmentation gradients. In contrast to expectations, however, the overall effects of fragmentation did not change with spatial extent. Conclusions Our results suggest that fragmentation can mitigate biodiversity loss immediately following habitat destruction, but that the benefits do not vary strongly with spatial extent in real‐world landscapes and at extents relevant to land management.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Current extent and future opportunities for living shorelines in Australia - Rebecca L. Morris; Erin Campbell-Hooper; Elissa Waters; Melanie J. Bishop; Catherine E. Lovelock; Ryan J. Lowe; Elisabeth M.A. Strain; Paul Boon; Anthony Boxshall; Nicola K. Browne; James T. Carley; Benedikt J. Fest; et al. (Science of The Total Environment, 2024)

Botulinum Neurotoxin Treatment Dynamics and Persistence Over 2 Years in Patients With Cervical Dystonia or Spasticity: A Retrospective Claims Database Analysis - David M. Simpson; Jonathan Bouchard; Simon Page; Dean Spurden; Seth Goldfarb; Atul T. Patel (Toxicon, 2024)

Acoustic backscattering at a tidal intrusion front - Christopher Bassett; Andone C. Lavery; David Ralston; W. Rockwell Geyer; Joseph T. Jurisa; Jim Thomson; David A. Honegger; Alexandra Simpson; Malcom E. Scully; Merrick C. Haller (Progress in Oceanography, 2023)

Norepinephrine depletion in the brain sex-dependently modulates aspects of spatial learning and memory in female and male rats - Ali Gheidi; Cameron J. Davidson; Serena C. Simpson; Majd A. Yahya; Nareen Sadik; Alixandria T. Mascarin; Shane A. Perrine (Psychopharmacology, 2023)

Do global change variables alter mangrove decomposition? A systematic review - Loraé T. Simpson; Samantha K. Chapman; Lance M. Simpson; Julia A. Cherry (Global Ecology and Biogeography, 2023)
Aim Global change is expected to modify the magnitude and trajectory of organic matter decomposition in mangrove ecosystems. Yet, the degree and direction of that change is unknown, especially considering the large C storage potential that mangroves provide. We performed a systematic review of primary literature to examine the relationships between genus‐specific litter quality, latitude or other global change proxies and decomposition of mangrove litter fractions. Location Global. Time Period 1976–2021. Taxon Mangroves. Methods We compiled a dataset of 480 decomposition rates, including species, litter fraction, latitude, and relevant biophysical data. We investigated the influence of genera, tissue type, latitude, and global change proxies on decomposition rates using linear models and qualitative approaches. We also performed calculations to determine the potential importance of the decomposition process on the root litter biomass C pool in the context of blue C significance. Results Collectively, latitudinal relationships suggest that factors other than temperature, such as tissue type and genus, may regulate decay rates within mangroves' distributional range. Decay rates of leaf litter, roots, and wood converged on a value of 0.009 ± 0.0005, 0.002 ± 0.0001, and 0.001 ± 0.0003, respectively, across continents and geomorphological settings. Our calculations suggest that small changes in decomposition rate will not elicit large changes in blue C storage potential. Conclusions The main drivers behind variability in mangrove biomass decay rates detected across the distributional range remain uncertain. However, the small latitudinal range that mangroves inhabit and the submerged environment within which litter decomposes suggest that decay depends on species‐specific responses or biotic interactions among species to global change drivers. Few studies have examined global change impacts directly, and variability in decay and lack of representation of some mangrove groups in the literature suggest that implications for blue C are important to consider.

Farmers’ valuation and willingness to pay for vaccines to protect livestock resources against priority infectious diseases in Ghana - Francis Sena Nuvey; Nick Hanley; Katherine Simpson; Daniel T. Haydon; Jan Hattendorf; Gloria Ivy Mensah; Kennedy Kwasi Addo; Bassirou Bonfoh; Jakob Zinsstag; Günther Fink (Preventive Veterinary Medicine, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The distribution of metal and petroleum-derived contaminants within sediments around oil and gas infrastructure in the Gippsland Basin, Australia - Sharon E. Hook; Scott Foster; Franziska Althaus; Douglas Bearham; Brad M. Angel; Andrew T. Revill; Stuart L. Simpson; Joanna Strzelecki; Tom Cresswell; Keith R. Hayes (Marine Pollution Bulletin, 2023)

ACMT Position Statement: End the Use of the Term “Excited Delirium” - Andrew I. Stolbach; Paul I. Dargan; Howard A. Greller; Richard J. Hamilton; Kelly Johnson-Arbor; Brian Patrick Murray; Daniel Ovakim; Laura Tormoehlen; Lewis S. Nelson; Sukhshant Atti; Jeffrey N. Bernstein; Caitlin Bonney; et al. (Journal of Medical Toxicology, 2023)

Nitrogen Addition Increases Freeze Resistance in Black Mangrove (Avicennia germinans) Shrubs in a Temperate-Tropical Ecotone - Ilka C. Feller; Uta Berger; Samantha K. Chapman; Emily M. Dangremond; Nicole G. Dix; J. Adam Langley; Catherine E. Lovelock; Todd Z. Osborne; Audrey C. Shor; Loraé T. Simpson (Ecosystems, 2023)

Trade-off between microbial carbon use efficiency and specific nutrient-acquiring extracellular enzyme activities under reduced oxygen - Ji Chen; Irene Cordero; Daryl L. Moorhead; Jennifer K. Rowntree; Loraé T. Simpson; Richard D. Bardgett; Hayley Craig (Soil Ecology Letters, 2023)

Inhibitory mechanisms on dry anaerobic digestion: Ammonia, hydrogen and propionic acid relationship - Ildefonso Rocamora; Stuart T. Wagland; Francis Hassard; Raffaella Villa; Miriam Peces; Edmon W. Simpson; Oliver Fernández; Yadira Bajón-Fernández (Waste Management, 2023)

A metagenomic-based study of two sites from the Barbadian reef system - S. Simpson; V. Bettauer; A. Ramachandran; S. Kraemer; S. Mahon; M. Medina; Y. Vallès; V. Dumeaux; H. Vallès; D. Walsh; M. T. Hallett (Coral Reefs, 2023)
We study the microbiome of sea water collected from two locations of the Barbadian coral reefs. The two sites differ in several environmental and ecological variables including their endogenous benthic community and their proximity to urban development and runoffs from inland watersheds. The composition of the microbial communities was estimated using whole genome DNA shotgun sequencing with adjuvant measurements of chemical and environmental qualities. Although both sites exhibit a similar degree of richness, the less urbanized site (Maycocks reef at Hangman’s Bay) has a strong concentration of phototrophs whereas the more urbanized location (Bellairs reef at Folkstone) is enriched for copiotrophs, macroalgal symbionts and marine-related disease-bearing organisms from taxa scattered across the tree of life. Our results are concordant with previous profiles of warm ocean surface waters, suggesting our approach captures the state of each coral reef site, setting the stage for longitudinal studies of marine microbiome dynamics in Barbados.

Marine invertebrates and noise - Marta Solé; Kenzo Kaifu; T. Aran Mooney; Sophie L. Nedelec; Frédéric Olivier; Andrew N. Radford; Mirella Vazzana; Matthew A. Wale; Jayson M. Semmens; Stephen D. Simpson; Giuseppa Buscaino; Anthony Hawkins; et al. (Frontiers in Marine Science, 2023)
Within the set of risk factors that compromise the conservation of marine biodiversity, one of the least understood concerns is the noise produced by human operations at sea and from land. Many aspects of how noise and other forms of energy may impact the natural balance of the oceans are still unstudied. Substantial attention has been devoted in the last decades to determine the sensitivity to noise of marine mammals—especially cetaceans and pinnipeds—and fish because they are known to possess hearing organs. Recent studies have revealed that a wide diversity of invertebrates are also sensitive to sounds, especially via sensory organs whose original function is to allow maintaining equilibrium in the water column and to sense gravity. Marine invertebrates not only represent the largest proportion of marine biomass and are indicators of ocean health but many species also have important socio-economic values. This review presents the current scientific knowledge on invertebrate bioacoustics (sound production, reception, sensitivity), as well as on how marine invertebrates are affected by anthropogenic noises. It also critically revisits the literature to identify gaps that will frame future research investigating the tolerance to noise of marine ecosystems.

Contrasting Effects of Nitrogen Addition on Leaf Photosynthesis and Respiration in Black Mangrove in North Florida - Matthew A. Sturchio; Jeff Chieppa; Lorae T. Simpson; Ilka C. Feller; Samantha K. Chapman; Michael J. Aspinwall (Estuaries and Coasts, 2023)

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Late Ordovician subsurface carbonates and fossil assemblages from the area immediately west and northwest of Peak Hill in central New South Wales and their regional correlation - Y. Y. Zhen; T. J. Wells; C. J. Simpson; J. Parslow (Australian Journal of Earth Sciences, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Bird rookery nutrient over-enrichment as a potential accelerant of mangrove cay decline in Belize - L. T. Simpson; S. W. J. Canty; J. R. Cissell; M. K. Steinberg; J. A. Cherry; I. C. Feller (Oecologia, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Unexpected shift from phytoplankton to periphyton in eutrophic streams due to wastewater influx - Nathanael T. Bergbusch; Nicole M. Hayes; Gavin L. Simpson; Peter R. Leavitt (Limnology and Oceanography, 2021)
Pollution with nitrogen (N) and phosphorous (P) impairs streams by favoring suspended algae and cyanobacteria over diatom‐rich periphyton. Recently, wastewater treatment plants have been upgraded to biological nutrient removal to eliminate both P and N (mainly NH 4 + ), although little is known of the effects of this effluent on flowing waters. Here, we used high performance liquid chromatography to quantify how the abundance and composition of phytoplankton and periphyton varied in response to both influx of effluent produced by biological nutrient removal and physico‐chemical conditions in small, turbid, P‐rich streams of the northern Great Plains. At the catchment scale, analysis with generalized additive models (GAMs) explained 40.5–62.6% of deviance in total phototroph abundance (as Chl a ) and 72.5–82.5% of deviance in community composition (as biomarker carotenoids) in both planktonic and benthic habitats when date‐ and site‐specific physico‐chemical parameters were used as predictors. In contrast, GAMs using wastewater input (as aqueous δ 15 N) as a predictor explained up to 50% of deviance in Chl a , and ~60% of deviance in community composition, in both suspended (51.6% of Chl a , 67.1% of composition) and attached communities (21.5% of Chl a , 58.8% of composition). Phytoplankton was replaced by periphyton within a 60‐km wastewater‐impacted reach due to dilution of streams by transparent effluent and addition of urban NO 3 − , although predominance of phytoplankton was re‐established after confluence with higher‐order streams. Overall, influx of effluent shifted turbid, phytoplankton‐rich streams to clear ecosystems with abundant epilithon by improving water transparency and providing NO 3 − to favor benthic diatoms and chlorophytes.

Mangrove Encroachment Alters Decomposition Rate in Saltmarsh Through Changes in Litter Quality - Loraé T. Simpson; Julia A. Cherry; Rachel S. Smith; Ilka C. Feller (Ecosystems, 2021)

Increasing whole-body energetic stress does not augment fasting-induced changes in human skeletal muscle - Hashim Islam; Alessandra Amato; Jacob T. Bonafiglia; Fasih A. Rahman; Nicholas Preobrazenski; Andrew Ma; Craig A. Simpson; Joe Quadrilatero; Brendon J. Gurd (Pflügers Archiv - European Journal of Physiology, 2021)

Zircon petrochronology in large igneous provinces reveals upper crustal contamination processes: new U–Pb ages, Hf and O isotopes, and trace elements from the Central Atlantic magmatic province (CAMP) - J. H. F. L. Davies; A. Marzoli; H. Bertrand; N. Youbi; M. Ernesto; N. D. Greber; M. Ackerson; G. Simpson; A.-S. Bouvier; L. Baumgartner; T. Pettke; F. Farina; et al. (Contributions to Mineralogy and Petrology, 2021)
Zircon occasionally crystallizes in evolved melt pockets in mafic large igneous province (LIP) magmas, and in these cases, it is used to provide high-precision age constraints on LIP events. The precision and accuracy of high-precision ages from LIPs are crucially important, because they may be implicated in mass extinctions. However, why zircon crystallizes in these magmas is not clearly understood, since their mafic compositions should limit zircon saturation. Here, we investigate the occurrence of zircon (and baddeleyite) in intrusive and extrusive mafic rocks from Central Atlantic Magmatic Province (CAMP) using petrography, trace-element analysis, Ti temperatures, Hf and oxygen isotopes, and high-precision U–Pb geochronology, along with petrological and thermal modeling. We provide new ages for CAMP sills that intruded into Paleozoic sediments in Brazil, indicating that the high and low Ti magmatism in this area occurred synchronously over 264 ± 57 ka. We show that upper crustal assimilation, especially of shales, during the emplacement of the CAMP likely led to zircon saturation. Assimilation of upper crustal sediments is also supported by high δ 18 O values and some rare negative εHf values in the zircon crystals. The only extrusive sample analyzed was the North Mountain basalt in Nova Scotia, Canada. This sample contains a large age variation in its zircon crystals (up to 4 Ma), and the older crystals have slightly more negative εHf values suggesting the presence of small (micron scale) xenocrystic cores associated with very late-stage sediment assimilation. However, the CAMP dataset as a whole suggests that the presence of xenocrystic cores is rare. Assuming no xenocrystic cores, and considering the zircon undersaturated nature of LIP mafic melts, the oldest zircon age clusters in a population should record the magma emplacement (or time when assimilation occurred), and the younger ages in a population are more likely to reflect Pb loss, especially given the high U concentrations of LIP zircon. Our identification of heterogeneous isotopic and elemental compositions in LIP zircon indicates that zircon in these magmas saturate in isolated minute melt pockets just before the system cools below its solidus.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Energetic Carrying Capacity of Submersed Aquatic Vegetation in Semi-Permanent Wetlands Important to Waterfowl in the Upper Midwest - Margaret C. Gross; Joseph D. Lancaster; John W. Simpson; Brendan T. Shirkey; Sarah E. McClain; Christopher N. Jacques; J. Brian Davis; Heath M. Hagy (Wetlands, 2020)

Nitrogen Enrichment Accelerates Mangrove Range Expansion in the Temperate–Tropical Ecotone - Emily M. Dangremond; Loraé T. Simpson; Todd Z. Osborne; Ilka C. Feller (Ecosystems, 2020)

Design of a Drug-Eluting Subcutaneous Implant of the Antiretroviral Tenofovir Alafenamide Fumarate - Solange M Simpson; Lakmini Widanapathirana; Jonathan T. Su; Samuel Sung; David Watrous; Jiang Qiu; Elizabeth Pearson; Alex Evanoff; Dipu Karunakaran; Jorge E. Chacon; Patrick F. Kiser (Pharmaceutical Research, 2020)
Purpose Sexual transmission of HIV has been clinically proven to be preventable with a once-daily oral tablet; however, missed doses dramatically increase the risk of HIV infection. Long-acting subcutaneous implants do not allow the user to miss a dose. A desirable long-acting drug-eluting implant can deliver a constant amount of drug, adjust the delivered dose, and be readily manufactured. We present a long-acting, subcutaneous implant design composed of tenofovir alafenamide hemifumarate (TAF) pellets loaded in a sealed polyether urethane tube for the prevention of HIV transmission. Methods Implants were prepared with pressed drug pellets and extruded polyurethane tubing. In vitro release rate of implants using different pellet formulations, rate-controlling membranes, and geometries were measured. Results Tenofovir alafenamide release appeared to be governed by a pseudo-steady state and followed a mass transport model of release from a cylindrical drug reservoir. Implant seal integrity was tested and confirmed using mechanical testing. The inclusion of sodium chloride in the pellet increased the release rate and reduced initial lag. The release was sustained for 100 days. Conclusions The release rate of tenofovir alafenamide mechanistically varied with geometry and rate controlling membrane composition. The polyether urethane implant presented herein is modular and tunable to adjust the release rate and duration of the TAF release.

MicroRNA-34a Acutely Regulates Synaptic Efficacy in the Adult Dentate Gyrus In Vivo - Birgitte Berentsen; Sudarshan Patil; Kine Rønnestad; Kevin M. Goff; Maciej Pajak; T. Ian Simpson; Karin Wibrand; Clive R. Bramham (Molecular Neurobiology, 2020)

The impact of acute and chronic exercise on Nrf2 expression in relation to markers of mitochondrial biogenesis in human skeletal muscle - Hashim Islam; Jacob T. Bonafiglia; Patrick C. Turnbull; Craig A. Simpson; Christopher G. R. Perry; Brendon J. Gurd (European Journal of Applied Physiology, 2020)

Envisioning a national invasive species information framework - Jamie K. Reaser; Annie Simpson; Gerald F. Guala; Jeffrey T. Morisette; Pam Fuller (Biological Invasions, 2020)
With a view toward creating a national Early Detection and Rapid Response Program (EDRR) program, the United States National Invasive Species Council Management Plan for 2016–2018 calls for a series of assessments of federal EDRR capacities, including the evaluation of “relevant federal information systems to provide the data and other information necessary for risk analyses/horizon scanning, rapid specimen identification, and rapid response planning.” This paper is a response to that directive. We provide an overview of information management needs for enacting EDRR and discuss challenges to meeting these needs. We then review the history of relevant US policy directives for advancing invasive species information systems and provide an overview of federal invasive species information system capacities, including current gaps and inconsistencies. We conclude with a summary of key principles and needs for establishing a national invasive species information framework. Our findings are consistent with earlier studies and, thus, emphasize the need to act on long-recognized needs. As a supplement to this paper, we have cataloged federal invasive species databases and information tools identified through this work.

Blue Carbon: an Additional Driver for Restoring and Preserving Ecological Services of Coastal Wetlands in Tampa Bay (Florida, USA) - Lindsey Sheehan; Edward T. Sherwood; Ryan P. Moyer; Kara R. Radabaugh; Stefanie Simpson (Wetlands, 2019)

Inbreeding depression causes reduced fecundity in Golden Retrievers - Erin T. Chu; Missy J. Simpson; Kelly Diehl; Rodney L. Page; Aaron J. Sams; Adam R. Boyko (Mammalian Genome, 2019)

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

Mangroves dramatically increase carbon storage after 3 years of encroachment - L. T. Simpson; C. M. Stein; T. Z. Osborne; I. C. Feller (Hydrobiologia, 2019)

Wetland Soil Co2 Efflux Along a Latitudinal Gradient of Spatial and Temporal Complexity - L.T. Simpson; T. Z. Osborne; I. C. Feller (Estuaries and Coasts, 2019)

Typification of Piper species (Piperaceae) in Southeast Asia, especially Thailand - C. Suwanphakdee; D. A. Simpson; T. R. Hodkinson; P. Chantaranothai (Kew Bulletin, 2018)

Environmental exposure and parental collection does not affect detection or semi-quantitative load assessment of bacteria in nasal swab specimens from children - Nada Townsi; Shannon J. Simpson; Chisha T. Sikazwe; Glenys R. Chidlow; Graham L. Hall; J. Jane Pillow; Andrew C. Wilson; David W. Smith; Ingrid A. Laing (Infectious Diseases, 2018)

Safety, tolerability and pharmacokinetics of GSK3008348, a novel integrin αvβ6 inhibitor, in healthy participants - Charlotte H. Maden; David Fairman; Michelle Chalker; Maria J. Costa; William A. Fahy; Nadia Garman; Pauline T. Lukey; Tim Mant; Simon Parry; Juliet K. Simpson; Robert J. Slack; Stuart Kendrick; et al. (European Journal of Clinical Pharmacology, 2018)

A cross correlation method for chemical profiles in minerals, with an application to zircons of the Kilgore Tuff (USA) - L. C. Probst; T. E. Sheldrake; M. J. Gander; G. Wallace; G. Simpson; L. Caricchi (Contributions to Mineralogy and Petrology, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Large‐scale bleaching of corals on the Great Barrier Reef - T. P. Hughes; J. T. Kerry; T. Simpson (Ecology, 2018)
In 2015–2016, record temperatures triggered a pan‐tropical episode of coral bleaching. In the southern hemisphere summer of March–April 2016, we used aerial surveys to measure the level of bleaching on 1,156 individual reefs throughout the 2,300 km length of the Great Barrier Reef, the world's largest coral reef system. The accuracy of the aerial scores was ground‐truthed with detailed underwater surveys of bleaching at 260 sites (104 reefs), allowing us to compare aerial and underwater bleaching data with satellite‐derived temperatures and with associated model predictions of bleaching. The severity of bleaching on individual reefs in 2016 was tightly correlated with the level of local heat exposure: the southernmost region of the Great Barrier Reef escaped with only minor bleaching because summer temperatures there were close to average. Gradients in nutrients and turbidity from inshore to offshore across the Great Barrier Reef had minimal effect on the severity of bleaching. Similarly, bleaching was equally severe on reefs that are open or closed to fishing, once the level of satellite‐derived heat exposure was accounted for. The level of post‐bleaching mortality, measured underwater after 7–8 months, was tightly correlated with the aerial scores measured at the peak of bleaching. Similarly, reefs with a high aerial bleaching score also experienced major shifts in species composition due to extensive mortality of heat‐sensitive species. Reefs with low bleaching scores did not change in composition, and some showed minor increases in coral cover. Two earlier mass bleaching events occurred on the Great Barrier Reef in 1998 and 2002, that were less severe than 2016. In 2016, 60% of corals affected) was four times higher in 2016. The geographic footprint of each of the three events is distinctive, and matches satellite‐derived sea surface temperature patterns. Our aerial surveys indicate that past exposure to bleaching in 1998 and 2002 did not lessen the severity of bleaching in 2016. This data set of aerial bleaching scores provides a historical baseline for comparison with future bleaching events. No copyright restrictions apply to the use of this data set other than citing this publication.

Carbon Storages along a Climate Induced Coastal Wetland Gradient - L. T. Simpson; T. Z. Osborne; L. J. Duckett; I. C. Feller (Wetlands, 2017)

Analysis of compound heterozygotes reveals that the mouse floxed Pax6 tm1Ued allele produces abnormal eye phenotypes - Natalie J. Dorà; Aaron J. F. Crookshanks; Karen K. Y. Leung; T. Ian Simpson; John O. Mason; David J. Price; John D. West (Transgenic Research, 2016)

Next-generation sequencing-based molecular diagnosis of 82 retinitis pigmentosa probands from Northern Ireland - Li Zhao; Feng Wang; Hui Wang; Yumei Li; Sharon Alexander; Keqing Wang; Colin E. Willoughby; Jacques E. Zaneveld; Lichun Jiang; Zachry T. Soens; Philip Earle; David Simpson; et al. (Human Genetics, 2015)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

Predicted responses of arctic and alpine ecosystems to altered seasonality under climate change - Jessica G Ernakovich; Kelly A. Hopping; Aaron B. Berdanier; Rodney T. Simpson; Emily J. Kachergis; Heidi Steltzer; Matthew D. Wallenstein (Global Change Biology, 2014)
Global climate change is already having significant impacts on arctic and alpine ecosystems, and ongoing increases in temperature and altered precipitation patterns will affect the strong seasonal patterns that characterize these temperature‐limited systems. The length of the potential growing season in these tundra environments is increasing due to warmer temperatures and earlier spring snow melt. Here, we compare current and projected climate and ecological data from 20 Northern Hemisphere sites to identify how seasonal changes in the physical environment due to climate change will alter the seasonality of arctic and alpine ecosystems. We find that although arctic and alpine ecosystems appear similar under historical climate conditions, climate change will lead to divergent responses, particularly in the spring and fall shoulder seasons. As seasonality changes in the Arctic, plants will advance the timing of spring phenological events, which could increase plant nutrient uptake, production, and ecosystem carbon (C) gain. In alpine regions, photoperiod will constrain spring plant phenology, limiting the extent to which the growing season can lengthen, especially if decreased water availability from earlier snow melt and warmer summer temperatures lead to earlier senescence. The result could be a shorter growing season with decreased production and increased nutrient loss. These contrasting alpine and arctic ecosystem responses will have cascading effects on ecosystems, affecting community structure, biotic interactions, and biogeochemistry.

Erratum to: Direct measurement of roots in soil for single and mixed species using a quantitative DNA-based method - Rebecca E. Haling; Richard J. Simpson; Alan C. McKay; Diana Hartley; Hans Lambers; Kathy Ophel-Keller; Sue Wiebkin; Herdina; Ian T. Riley; Alan E. Richardson (Plant and Soil, 2013)

Consistent proportional macronutrient intake selected by adult domestic cats (Felis catus) despite variations in macronutrient and moisture content of foods offered - Adrian K. Hewson-Hughes; Victoria L. Hewson-Hughes; Alison Colyer; Andrew T. Miller; Simon R. Hall; David Raubenheimer; Stephen J. Simpson (Journal of Comparative Physiology B, 2013)

The Benefits of Spatially Targeted Water Level Management for Salinity Reduction in a Coastal Aquifer - I. P. Holman; K. R. Rushton; T. B. Simpson (Water Resources Management, 2013)

Erratum to: Beyond knockouts: cre resources for conditional mutagenesis - Stephen A. Murray; Janan T. Eppig; Damian Smedley; Elizabeth M. Simpson; Nadia Rosenthal (Mammalian Genome, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Beyond knockouts: cre resources for conditional mutagenesis - Stephen A. Murray; Janan T. Eppig; Damian Smedley; Elizabeth M. Simpson; Nadia Rosenthal (Mammalian Genome, 2012)

Eremochloa renvoizei, a new species of Poaceae from Thailand - P. Traiperm; T. Boonkerd; P. Chantaranothai; D. A. Simpson (Kew Bulletin, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Above‐ and belowground responses of arctic tundra ecosystems to altered soil nutrients and mammalian herbivory - Laura Gough; John C. Moore; Gauis R. Shaver; Rodney T. Simpson; David R. Johnson (Ecology, 2012)
Theory and observation indicate that changes in the rate of primary production can alter the balance between the bottom‐up influences of plants and resources and the top‐down regulation of herbivores and predators on ecosystem structure and function. The Exploitation Ecosystem Hypothesis (EEH) posited that as aboveground net primary productivity (ANPP) increases, the additional biomass should support higher trophic levels. We developed an extension of EEH to include the impacts of increases in ANPP on belowground consumers in a similar manner as aboveground, but indirectly through changes in the allocation of photosynthate to roots. We tested our predictions for plants aboveground and for phytophagous nematodes and their predators belowground in two common arctic tundra plant communities subjected to 11 years of increased soil nutrient availability and/or exclusion of mammalian herbivores. The less productive dry heath (DH) community met the predictions of EEH aboveground, with the greatest ANPP and plant biomass in the fertilized plots protected from herbivory. A palatable grass increased in fertilized plots while dwarf evergreen shrubs and lichens declined. Belowground, phytophagous nematodes also responded as predicted, achieving greater biomass in the higher ANPP plots, whereas predator biomass tended to be lower in those same plots (although not significantly). In the higher productivity moist acidic tussock (MAT) community, aboveground responses were quite different. Herbivores stimulated ANPP and biomass in both ambient and enriched soil nutrient plots; maximum ANPP occurred in fertilized plots exposed to herbivory. Fertilized plots became dominated by dwarf birch (a deciduous shrub) and cloudberry (a perennial forb); under ambient conditions these two species coexist with sedges, evergreen dwarf shrubs, and Sphagnum mosses. Phytophagous nematodes did not respond significantly to changes in ANPP, although predator biomass was greatest in control plots. The contrasting results of these two arctic tundra plant communities suggest that the predictions of EEH may hold for very low ANPP communities, but that other factors, including competition and shifts in vegetation composition toward less palatable species, may confound predicted responses to changes in productivity in higher ANPP communities such as the MAT studied here.

A regional real-time debris-flow warning system for the District of North Vancouver, Canada - Matthias Jakob; T. Owen; T. Simpson (Landslides, 2012)

A microsatellite linkage map for the cultivated strawberry (Fragaria × ananassa) suggests extensive regions of homozygosity in the genome that may have resulted from breeding and selection - D. J. Sargent; T. Passey; N. Šurbanovski; E. Lopez Girona; P. Kuchta; J. Davik; R. Harrison; A. Passey; A. B. Whitehouse; D. W. Simpson (Theoretical and Applied Genetics, 2012)

A doxycycline-inducible, tissue-specific aromatase-expressing transgenic mouse - Jenny D. Y. Chow; John T. Price; Margaret M. Bills; Evan R. Simpson; Wah Chin Boon (Transgenic Research, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Notes on the genus Ischaemum (Poaceae) - P. Traiperm; T. Boonkerd; P. Chantaranothai; D. A. Simpson (Kew Bulletin, 2012)

Consequences of frugivore‐mediated seed dispersal for the spatial and genetic structures of a neotropical palm - J. CHOO; T. E. JUENGER; B. B. SIMPSON (Molecular Ecology, 2012)
The idiosyncratic behaviours of seed dispersers are important contributors to plant spatial associations and genetic structures. In this study, we used a combination of field, molecular and spatial studies to examine the connections between seed dispersal and the spatial and genetic structures of a dominant neotropical palm Attalea phalerata. Field observation and genetic parentage analysis both indicated that the majority of A. phalerata seeds were dispersed locally over short distances ( 10 m) from maternal palms. Seedlings were also spatially aggregated with juveniles. These patterns are probably associated with the dispersal of seeds by rodents and the survival of recruits at specific microsites or neighbourhoods over successive fruiting periods. Our cross‐cohort analyses found palms in older cohorts and cohort pairs were associated with a lower proportion of offspring and sibling neighbours and exhibited weaker spatial and genetic structures. Such patterns are consistent with increased distance‐ and density‐dependent mortality over time among palms dispersed near maternal palms or siblings. The integrative approaches used for this study allowed us to infer the importance of seed dispersal activities in maintaining the aggregated distribution and significant genetic structures among A. phalerata palms. We further conclude that distance‐ and density‐dependent mortality is a key postdispersal process regulating this palm population.

Direct measurement of roots in soil for single and mixed species using a quantitative DNA-based method - Rebecca E. Haling; Richard J. Simpson; Alan C. McKay; Diana Hartley; Hans Lambers; Kathy Ophel-Keller; Sue Wiebkin; Herdina; Ian T. Riley; Alan E. Richardson (Plant and Soil, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

Laboratory Animal Management Assistant (LAMA): a LIMS for active research colonies - Marko Milisavljevic; Taryn Hearty; Tony Y. T. Wong; Elodie Portales-Casamar; Elizabeth M. Simpson; Wyeth W. Wasserman (Mammalian Genome, 2010)

Paleolimnological evidence of the effects on lakes of energy and mass transfer from climate and humans - Peter R. Leavitt; S. C. Fritz; N. J. Anderson; P. A. Baker; T. Blenckner; L. Bunting; J. Catalan; D. J. Conley; W. O. Hobbs; E. Jeppesen; A. Korhola; S. McGowan; et al. (Limnology and Oceanography, 2009)
The premise of this article is that climate effects on lakes can be quantified most effectively by the integration of process‐oriented limnological studies with paleolimnological research, particularly when both disciplines operate within a common conceptual framework. To this end, the energy (E)‐mass ( m ) flux framework (E m flux) is developed and applied to selected retrospective studies to demonstrate that climate variability regulates lake structure and function over diverse temporal and spatial scales through four main pathways: rapid direct transfer of E to the lake surface by irradiance, heat, and wind; slow indirect effects of E via changes in terrestrial development and subsequent m subsidies to lakes; direct influx of m as precipitation, particles, and solutes from the atmosphere; and indirect influx of water, suspended particles, and dissolved substances from the catchment. Sedimentary analyses are used to illustrate the unique effects of each pathway on lakes but suggest that interactions among mechanisms are complex and depend on the landscape position of lakes, catchment characteristics, the range of temporal variation of individual pathways, ontogenetic changes in lake basins, and the selective effects of humans on m transfers. In particular, preliminary synthesis suggests that m influx can overwhelm the direct effects of E transfer to lakes, especially when anthropogenic activities alter m subsidies from catchments.

Sequence stratigraphy of Jurassic strata in the lower Surat Basin succession, Queensland - K. L. Hoffmann; J. M. Totterdell; O. Dixon; G. A. Simpson; A. T. Brakel; A. T. Wells; J. L. Mckellar (Australian Journal of Earth Sciences, 2009)

Effect of Nutrition on Toxicity of Contaminants to the Epibenthic Amphipod Melita plumulosa - D. A. Spadaro; T. Micevska; S. L. Simpson (Archives of Environmental Contamination and Toxicology, 2008)

Effect of Nutrition on Toxicity of Contaminants to the Epibenthic Amphipod Melita plumulosa - D. A. Spadaro; T. Micevska; S. L. Simpson (Archives of Environmental Contamination and Toxicology, 2008)

Effects of Light on Microalgae Concentrations and Selenium Uptake in Bivalves Exposed to Selenium-Amended Sediments - D. Schlenk; G. Batley; C. King; J. Stauber; M. Adams; S. Simpson; W. Maher; J. T. Oris (Archives of Environmental Contamination and Toxicology, 2007)

Encapsulation of protein nanoparticles into uniform-sized microspheres formed in a spinning oil film - W. Thomas Leach; Dale T. Simpson; Tibisay N. Val; Zhongshui Yu; Kwon T. Lim; Eun J. Park; Robert O. Williams; Keith P. Johnston (AAPS PharmSciTech, 2005)

Childhood Cancer and Social Contact: the Role of Paternal Occupation (United Kingdom)* - Nicola T. Fear; Jill Simpson; Eve Roman (Cancer Causes & Control, 2005)

Measurements of Trace Gases in the Inflow of South China Sea Background Air and Outflow of Regional Pollution at Tai O, Southern China - T. Wang; H. Guo; D. R. Blake; Y. H. Kwok; I. J. Simpson; Y. S. Li (Journal of Atmospheric Chemistry, 2005)

Clinical validation of the NeuroScreen - Ronald J Ellis; Scott R Evans; David B Clifford; Lauren R Moo; Justin C McArthur; Ann C Collier; Constance Benson; Ron Bosch; David Simpson; Constantin T Yiannoutsos; Yijun Yang; Kevin Robertson; et al. (Journal of NeuroVirology, 2005)

A genetic linkage map of microsatellite, gene-specific and morphological markers in diploid Fragaria - D. J. Sargent; T. M. Davis; K. R. Tobutt; M. J. Wilkinson; N. H. Battey; D. W. Simpson (Theoretical and Applied Genetics, 2004)

COX-1, COX-2 and the topical effect in NSAID-induced enteropathy - C. M. Hotz-Behofsits; M. J. M. Walley; R. Simpson; I. T. Bjarnason (Inflammopharmacology, 2003)

Effects of administration of somatostatin‐14 and immunoneutralization of somatostatin on endocrine and growth responses in rainbow trout - B. C. Peterson; P. R. Simpson; K. D. Cain; R. H. Hardy; G. T. Schelling; T. L. Ott (Journal of Fish Biology, 2003)
Injection of somatostatin‐14 (SS‐14) at 5 ng g −1 body mass (BM) into rainbow trout Oncorhynchus mykiss decreased ( P r 2 = 0·54) levels of growth hormone (GH) (1·5 ± 0·9 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time when compared to controls. Somatostatin‐14 at 50 ng g −1 BM also decreased ( P = 0·064, q uadratic; r 2 = 0·30) levels of GH (3·6 ± 2·1 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time compared to controls. In a second study, passive immunization against SS‐14 (1 : 25 dose) increased ( P = 0·10, cubic, r 2 = 0·12) levels of GH (11·0 ± 4·8 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time. Passively immunizing against SS‐14 (1 : 50 dose) increased ( P r 2 = 0·10) levels of GH (8·2 ± 2·3 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time compared to controls. Overall, in the active immunization study there was no difference ( P > 0·10) in specific growth rate ( G ) or feed conversion ratio ( FCR ) between the three treatment groups during the 9 weeks of the study. Only four of the fish immunized against SS‐14, however, developed antibody titres against SS. Compared to controls, these fish exhibited a G of 0·89 ± 0·09 v. 0·56 ± 0·09% per 3 weeks and FCR of 0·80 ± 0·04 v. 1·20 ± 0·05 g g −1 . In SS‐14 immunized fish, levels of GH decreased ( P P G and FCR is dependent upon generation of antibody titres.

The regulation of virulence in phytopathogenic Erwinia species: quorum sensing, antibiotics and ecological considerations - Neil A. Whitehead; Joseph T. Byers; Paul Commander; Mark J. Corbett; Sarah J. Coulthurst; Lee Everson; Abigail K.P. Harris; Clare L. Pemberton; Natalie J.L. Simpson; Holly Slater; Debra S. Smith; Martin Welch; et al. (Antonie van Leeuwenhoek, 2002)

Towards A Long-Term Integrated Monitoring Programme In Europe: Network Design in Theory and Practice - T. W. Parr; M. Ferretti; I. C. Simpson; M. Forsius; E. Kovács-Láng (Environmental Monitoring and Assessment, 2002)

Assessment of the biological health of the Brantas River, East Java, Indonesia using the Australian River Assessment System (AUSRIVAS) methodology - Sri Sudaryanti; Yulinah Trihadiningrum; Barry T Hart; Peter E. Davies; Chris Humphrey; Richard Norris; Justen Simpson; Lisa Thurtell (Aquatic Ecology, 2001)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Rhizogenesis in Forsythia×intermedia and Syringa vulgaris ; application of a simple internode experimental system - T. R. Marks; S. E. Simpson (Plant Cell Reports, 2000)

Objective Response Detection in an Electroencephalogram During Somatosensory Stimulation - David M. Simpson; Carlos J. Tierra-Criollo; Renato T. Leite; Eduardo J. B. Zayen; Antonio F. C. Infantosi (Annals of Biomedical Engineering, 2000)

Genomic organisation of the human chordin gene and mutation screening of candidate Cornelia de Lange syndrome genes - M. Smith; S. Herrell; M. Lusher; L. Lako; C. Simpson; A. Wiestner; R. Skoda; M. Ireland; T. Strachan (Human Genetics, 1999)

Revised nomenclature for strain 129 mice - Michael F.W. Festing; Elizabeth M. Simpson; Muriel T. Davisson; Larry E. Mobraaten (Mammalian Genome, 1999)

Genomic organisation of the human chordin gene and mutation screening of candidate Cornelia de Lange syndrome genes - M. Smith; S. Herrell; M. Lusher; L. Lako; C. Simpson; A. Wiestner; R. Skoda; M. Ireland; T. Strachan (Human Genetics, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Announcement - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Erratum - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

An investigation of the temporal induction of cytokine mRNAs in LPS-challenged thioglycollate-elicited murine peritoneal macrophages using the reverse transcription polymerase chain reaction - A. E. C. M. Simpson; P. T. Tomkins; K. L. Cooper (Inflammation Research, 1997)

Congo/Crimean Haemorrhagic Fever virus from Iraq 1979: I. Morphology in BHK21 cells - D. S. Ellis; T. Southee; G. Lloyd; G. S. Platt; Nicola Jones; Susan Stamford; E. T. W. Bowen; D. I. H. Simpson (Archives of Virology, 1981)